The impact of cross-border mergers and acquisitions on the acquirers' R & D Firm-level evidence - Joel Stiebale (International Journal of Industrial Organization, 2013)
This paper provides empirical evidence on the relationship between cross-border acquisitions and innovation activities of the acquirer. For the empirical analysis a unique firm-level data set is constructed that combines survey data for German firms with a merger and acquisition database. After a cross-border acquisition, investing firms display a higher rate of domestic expenditures for research and development. Controlling for endogeneity of foreign acquisitions by estimating a two-equation system with limited dependent variables and applying instrumental variable techniques it is found that part of this correlation stems from a causal effect. The estimated effects are robust towards alternative identification strategies and are higher in industries with high knowledge intensity. The analysis is complemented by an investigation of the effects on tangible investment spending and by a comparison of the effects of cross-border acquisitions to those of greenfield foreign direct investments and domestic acquisitions.
Keywords: D21; F23; G34; C31; O31; O33; 330; Multinational enterprises; Mergers and acquisitions; Innovation